Systematic identification of low voltage-high frequency electrogram zones at sites of left atrial reentrant tachycardia termination. (19th May 2022) - Merino, JL; Kim, S; Sanroman, M; Castrejon, S; Relan, J; De La Vieja Alarcon, JJ; Martinez Cossiani, M; Cervantes, C; Carton, A; Rivero Santana, B; Tauber Molina, P
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Abbott Background: Localization of the narrow isthmus of conduction of left atrial local and macro reentrant tachycardia (LAMRT) circuits within scar tissue is challenging. (Panel A). Near-field (NF) electrograms are often obscured by and difficult to distinguish from far-field (FF) activation. The peak frequency (PF) associated with bipolar electrograms is a novel parameter which may distinguish between NF and FF signals. (Panel B). However, the potential value of PF for LAMRT ablation has never been evaluated. Purpose: 1) To quantify the percentage of LA surface with low voltage (LV) and NF signals. 2) To study the proportion of LAMRT ablation sites which were located within a LV-NF region or in the vicinity of it (<10 mm away). Methods: LART bipolar voltage and activation maps were generated with a 16-pole grid catheter (HD-Grid) during tachycardia. (Panels A, B). PF maps were retrospectively computed (Panels C, D). LV zones were defined according to a cutoff <0.3mV. Four different PF cut-off values (>250, >300, >350 and >400 Hz) were assessed in the delineation of overlapping LV-NF regions. (Panel E) Results: 16 consecutive patients with 24 LAMRT's targeted for ablation were prospectively enrolled. 21/24 LAMRT's were terminated by radiofrequency application. (Panel F). The LV area represented 47.7±14% of the LA surface. The LV-NF area represented 8.2±6.2%, 5.2±5.4%, 3.4±7.4% and 3.3±4.1% of the LA surface by using 250, 300, 350, and 400 Hz PF cutoffs respectively. There were 2.1±1 (range 0-3), 0.9±0.8(range 0-3), 0.5±0.6 (range 0-2) and 0.5±0.6 (range 0-2) LV-NF areas per patient using 250, 300, 350 and 400 Hz PF cutoffs respectively. At the optimal PF cutoff > 250Hz and voltage < 0.3mV, the site of tachycardia termination by radiofrequency application was found inside of a LV-NF region in 13/21 LAMRTs (sensitivity 68.4%), and within 1cm of a LV-NF region in 19/21 LAMRTs (sensitivity 89.5%) respectively. Conclusion: 1. Left atrial reentry termination sites by radiofrequency application are often within or nearby LV-NF areas as identified by the PF and voltage analysis of bipolar electrograms. 2. Beyond conventional substrate mapping, the systematic identification of high frequency activity within the low voltage zone holds promise for rapid identification of isthmus conduction critical to LAMRTs.